The impact of gender ideology on the performance of gender-congruent citizenship behaviors. Issue 4 (8th August 2017) - Clarke, Heather M.; Sulsky, Lorne M.
ABSTRACT: Because organizational citizenship behavior (OCB) performance contributes to overall performance ratings and failure to perform expected behaviors detracts from performance ratings, it is important to examine whether men and women perform OCBs in stereotypically expected ways. Published studies have evidenced both a presence and an absence of gender differences in OCB performance. With a view to explaining this ambiguity, this article reports the results of a study examining gender ideology as a moderator of the effects of gender on the performance of gender-congruent OCBs (i.e., helping for women and civic virtue for men). Survey data from participants and their coworkers across a wide range of jobs and organizations revealed that gender ideology moderated the effects of gender on the performance of gender-congruent OCBs.